The New Model of Improvement Assistance of School Quality Service: A Mix-Method Study - Dera Nugraha; Mochammad Devi Cahya Ruhimat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This research aims to describe the improvement of school quality and promote it as a new model. Adopting an explanatory sequential design, the research was conducted over 149 days at SDIT and SMPIT Al-Falah Cirebon, involving 41 teachers and educational staff, as well as 212 parents. The improvement of school service quality was successful, evidenced by the change in parental satisfaction scores from <30% in the pre-development phase to >90% after the development. The success was discussed as a model to illustrate the evaluation of the school's objective conditions, designing and implementing school improvement programs, and measuring the success of school improvement programs effectively. Instead of relying on theoretical strength, parts of this research are filled with detailed prototypes of direct actions. Thus, the findings of this research can serve as a comprehensive reference for systematic school improvement. Due to its advantages, the results of this research promise significant value as it can serve as a model for the comprehensive improvement of school service quality that can be easily adopted by policymakers, consultants, and education practitioners in developing countries around the world.